Pengembangan Kompetensi Akuntansi dan Perpajakan Siswa SMK Mitra Bakti Husada – Bekasi - Widiyanti Rahayu Budi Astuti; Dewi Gunherani; Muliyani Muliyani; Sri Agustini; Fithrah Kamaliyah (S1 Accounting Program, Universitas Pamulang, 2020)
Professional competence as a pharmacist assistant really needs to be equipped with accounting and tax knowledge. Entering the business world, inevitably, in order to be successful, it must be done professionally, namely equipped with the skills to manage finances and taxes, so that in managing finances, students need to be equipped with this knowledge. The training programs that will be provided are accounting and tax. The program was chosen because it was considered important and was expected to provide education to these students. Accounting and tax materials are important materials as a provision for them to increase their ability to become entrepreneurs. By mastering accounting and taxes, it is expected that they can manage their business by compiling accounting and tax (fiscal) financial reports according to applicable standards.